Internalisasi Nilai Entrepreunership Berbasis Kearifan Lokal Melalui Matakuliah Kewirausahaan pada Mahasiswa MPI IAIN Kerinci - Wisda, Rini Syevyilni; Harmalis, Harmalis (Paedagogie, 2026)
This study aims to describe the internalization of local wisdom-based entrepreneurial values ​​through classroom learning in the entrepreneurship course at the Islamic Education Management (MPI) Department. The research method used was a qualitative descriptive approach. Data collection techniques included interviews, observation, and documentation. Data were analyzed through several stages, starting with data reduction, data presentation, and drawing conclusions/verifying the findings. The results of the study indicate that the internalization of entrepreneurial values ​​applied in the Islamic Education Management Department through adaptive classroom learning in the entrepreneurship course. The internalized values ​​are independence, creativity, courage to initiate, and risk-taking, centered on actions (application), leadership (cooperation), and hard work. The stages of internalization include role models, guidance, direction, and mentoring.